Original paperExpression of HIF-1 regulated proteins vascular endothelial growth factor, carbonic anhydrase IX and hypoxia inducible gene 2 in hemangioblastomas - Li, Mei; Song, Jie; Pytel, Peter (Folia Neuropathologica, 2014)
Introduction: Hemangioblastomas occur as sporadic or as von Hippel-Lindau syndrome (VHL) associated tumors. In both settings, activation of the VHL-HIF-1 (hypoxia induced factor) pathway is thought to be important in tumor biology. Material and methods: We performed immunohistochemical studies on 23 hemangioblastomas, 13 meningiomas and 4 hemangiopericytomas to evaluate expression of the VHL-HIF-1 regulated proteins vascular endothelial growth factor (VEGF), carbonic anhydrase IX (CAIX) and hypoxia inducible gene 2 (HIG-2). Results: Hemangioblastomas showed significantly higher expression of CAIX and VEGF than the other tested tumors. They showed strong membranous expression of CAIX in a pattern identical to that observed in clear cell renal cell carcinomas (CCRCC). Interestingly, hemangioblastomas lacked significant reactivity for HIG-2. Conclusions : The VHL-HIF-1 regulated genes VEGF and CAIX are expressed in hemangioblastomas but significant HIG-2 expression is not observed. Carbonic anhydrase IX staining in particular may be a helpful marker of hemangioblastomas but does not aid in the distinction from CCRCC.